2001
DOI: 10.1530/eje.0.1450053
|View full text |Cite
|
Sign up to set email alerts
|

Body mass, plasma leptin, glucose, insulin and C-peptide in offspring of diabetic and non-diabetic mothers

Abstract: Objective: The aim was to investigate the relationship between body mass index (BMI), plasma leptin, glucose, insulin and C-peptide levels in the offspring of diabetic mothers (DM) and non-diabetic healthy mothers (HM). Design: Seventy-two offspring (37 girls and 35 boys, age 4±20 years) of DM were investigated in a prospective study. Those 14±16 years old (Tanner stage II±IV) were compared with age-matched offspring of HM (33 girls and 33 boys). Results: BMI strongly correlated with plasma leptin concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
2
12
0
2
Order By: Relevance
“…Placental production of leptin might be responsible for hyperinsulinemia in the offspring of DM mother. [20]…”
Section: Discussionmentioning
confidence: 99%
“…Placental production of leptin might be responsible for hyperinsulinemia in the offspring of DM mother. [20]…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies describe the association of intrauterine exposure to diabetes with overweight and/or obesity in infants (3, 10, 26), children (1,4,8,9), and adolescents (11,13), obesity only partially contributes to insulin resistance and impaired glucose tolerance (IGT). More recently, Goran et al (16) reported that among overweight Latino children with a family history of T2DM, IGT was more prevalent in those children who were exposed to gestational diabetes; this association was not influenced by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a prior study by Plagemann et al (7), in our GDM offspring cohort, low birth weight was not associated with childhood obesity. The focus of most studies of diabetic pregnancies has been on preexisting type 1 or type 2 diabetes (4,6,18,19), or populations with preexisting and gestational diabetes were combined (20,21,4). Here, we explicitly excluded women with preexisting diabetes because diabetic vascular disorders may cause placental dysfunction and intrauterine growth retardation.…”
Section: Birth Weight and Childhood Overweightmentioning
confidence: 99%